The World Management Survey at 18: lessons and the way forward. (29th June 2021) - Scur, Daniela; Sadun, Raffaella; Van Reenen, John; Lemos, Renata; Bloom, Nicholas
Abstract: Understanding how differences in management 'best practices' affect organizational outcomes has been a focus of both theoretical and empirical work in the fields of management, sociology, economics, and public policy. The World Management Survey (WMS) project was born almost two decades ago with the main goal of developing a new systematic measure of management practices being used in organizations. The WMS has contributed to a body of knowledge around how managerial structures, not just managerial talent, relate to organizational performance. Over 18 years of research, a set of consistent patterns have emerged and spurred new questions. We present a brief overview of what we have learned in terms of measuring and understanding management practices and condense the implications of these findings for policy. We end with an outline of what we see as the path forward for both research and policy implications of this research programme.